The Importance of Lifelong Learning of Traditional Foods and Nutrition and the Role of Real and Virtual Information Organizations - Yalvac, Mesut; Soykut, Gunsu (Progress in Nutrition, 2020)
Traditional foods and connecting the concepts of lifelong learning and real and virtual information organizations is the main focus of this review/opinion paper. Encouraging empowerment of these concepts is believed to improve the nutritional status of all people among the society. In this review/opinion paper, it has been aimed to accentuate the importance of advancing real and virtual information organizations to the highest quality as well as lifelong learning programs and services that support and improve use of traditional foods of all people within different age groups, genders and socioeconomic status in the society. Documentary source analysis, descriptive research methods and data collection from scientific literature and documents techniques were used in the study. Topics of this study are subjected to review under the headings of “Traditional foods and nutrition concept”, “Lifelong learning concept”, “European Union concept and perspective of lifelong learning”, “The role and importance of real and virtual information organizations as centers of lifelong learning for traditional foods and nutrition”.